Diversification for an inclusive and resilient agri-food system in Kenya - Ooro, Patrick; Waswa, Boaz Shaban; Nchanji, Eileen Bogweh (2023)
The impacts of climate change in Eastern and Southern Africa (ESA), are already well known to farmers. Climate change affects women more negatively compared to men in five impact areas: (i) agricultural production; (ii) food and nutrition security; (iii) health; (iv) water and energy; (v) climate-related disaster, migration, and conflict. Over 2 million people in Kenya face the threat of food insecurity due to climate change. Maize production is particularly vulnerable to climate change. It is projected to face not only 15% climate-related declines in yield without adaptation but also challenges from diminished cropland suitability and poor agronomic inputs and management; degraded environmental bases with declining soil fertility and degraded water systems are already apparent. Given that maize-mixed systems cover over 75% of the cropping land in many places, it is critical to build climate resilience and derisk through diversification.